Design, Construction and Expression of Spike Highly Conserved Region (HCR) SARS-CoV-2 and Cholera Toxin Subunit B Fusion Protein in Lactococcus lactis NZ3900: Construction of recombinant plasmid in Lactococcus lactis - Kesuma, Suryanata; Adianingsih, Oktavia Rahayu; Winarsih, Sri; Widodo, Nashi; Yurina, Valentina (Journal of Tropical Life Science, 2025)
Prevention of SARS-CoV-2 transmission has primarily been achieved through vaccination, which is generally administered via injection and may cause discomfort. No commercially available SARS-CoV-2 vaccines can be administered via the mucosal route. However, recent advancements have demonstrated that vaccination with Lactococcus lactis enables vaccine delivery through the mucosa. A promising target for SARS-CoV-2 vaccine materials is the highly conserved region (HCR) of the SARS-CoV-2 spike (SARS-CoV-2 HCR Spike). Vaccine efficacy is enhanced by adding Cholera Toxin Subunit B (CTB) as an adjuvant. HCR and CTB proteins were recombinantly fused using a synthetic gene with optimized codons. This study aimed to construct a fusion protein of the SARS-CoV-2 spike protein and CTB in L. lactis strain NZ3900. The construction and expression of fusion proteins were analyzed using sequencing and protein electrophoresis. Codon optimization resulted in a Codon Adaptation Index value of 0.93 and a GC content of 27.06%. The cloning results revealed the formation of L. lactis colonies expressing the Fusion protein of the SARS-CoV-2 HCR Spike and CTB, which formed yellow colonies on the selection Elicker medium. PCR and sequencing confirmed the presence of the hcr-ctb gene, with a length of 981 bp and 100% sequence similarity. The Fusion protein of the SARS-CoV-2 HCR Spike and CTB was successfully expressed with a molecular weight of >35 kDa. In conclusion, we successfully constructed a Fusion protein of the SARS-CoV-2 HCR Spike and CTB in L. lactis NZ3900 as a potential vaccine candidate for oral administration to prevent SARS-CoV-2 infection.